Microstructure and mechanical properties of wire + arc additively manufactured 2024 aluminum alloy components: As-deposited and post heat-treated. (April 2019) - Qi, Zewu; Qi, Bojin; Cong, Baoqiang; Sun, Hongye; Zhao, Gang; Ding, Jialuo
Abstract: Restricted by the type of commercial aluminum wire, 2024 aluminum alloy cannot be built through conventional single wire + arc additive manufacturing technology. By simultaneously feeding two wires (ER2319 and ER5087) and adjusting the wire feed speed, 2024 aluminum alloy deposits can be achieved with double - wire + arc additive manufacturing process. Heat treatment procedures (solution + natural/artificial aging) were conducted for further improving the properties. The microstructure and mechanical properties of as-deposited and heat-treated 2024 aluminum alloy deposits were tested and analyzed. The microstructure differed in different conditions. Obvious dendrite morphology in as-deposited condition disappeared after heat treatment, and the phases turned to be α -Al + Al2 Cu from α -Al + Al2 Cu + Al2 CuMg. After heat treatment, layer distributing characteristics of the phases became obvious. Post-deposition heat treatment can improve the micro hardness, strength and horizontal elongation of WAAM 2024 aluminum alloy deposits. The elongation along vertical direction decreased.